Comparison of Aspirin and Benorylate in the Treatment of Rheumatoid Arthritis. Issue 5812 (27th May 1972) - Beales, D. L.; Burry, H. C.; Grahame, R.
Abstract : In a double-blind between-patient study of aspirin and benorylate carried out in 72 outpatients with rheumatoid arthritis, benorylate 4 g twice daily was shown to be an effective analgesic and anti-inflammatory drug, its effects being indistinguishable from those of aspirin 1·2 g four times daily. Compared with the pretreatment values both drugs produced a statistically significant improvement (P < 0·01) in functional grade, overall pain, articular index, and grip strength at the end of the first and second weeks. The overall incidence of side effects was less with benorylate, though this difference was not significant at the 5% level.